The Macroeconomic Impact of Increasing Investments in Malaria Control in 26 High Malaria Burden Countries: An Application of the Updated EPIC Model - Edith Patouillard; Seoni Han; Jeremy Lauer; Mara Barschkett; Jean-Louis Arcand (Kerman University of Medical Sciences, 2023)
Background  Malaria remains a major public health problem. While globally malaria mortality affects predominantly young children, clinical malaria affects all age groups throughout life. Malaria not only threatens health but also child education and adult productivity while burdening government budgets and economic development. Increased investments in malaria control can contribute to reduce this burden but have an opportunity cost for the economy. Quantifying the net economic value of investing in malaria can encourage political and financial commitment.Methods  We adapted an existing macroeconomic model to simulate the effects of reducing malaria on the gross domestic product (GDP) of 26 high burden countries while accounting for the opportunity costs of increased investments in malaria. We compared two scenarios differing in their level of malaria investment and associated burden reduction: sustaining malaria control at 2015 intervention coverage levels, time at which coverage levels reached their historic peak and scaling-up coverage to reach the 2030 global burden reduction targets. We incorporated the effects that reduced malaria in children and young adolescents may have on the productivity of working adults and on the future size of the labour force augmented by educational returns, skills, and experience. We calibrated the model using estimates from linked epidemiologic and costing models on these same scenarios and from published country-specific macroeconomic data.Results  Scaling-up malaria control could produce a dividend of US$ 152 billion in the modelled countries, equivalent to 0.17% of total GDP projected over the study period across the 26 countries. Assuming a larger share of malaria investments is paid out from domestic savings, the dividend would be smaller but still significant, ranging between 0.10% and 0.14% of total projected GDP. Annual GDP gains were estimated to increase over time. Lower income and higher burden countries would experience higher gains.Conclusion  Intensified malaria control can produce a multiplied return despite the opportunity cost of greater investments.